Mouse hepatitis coronavirus replication induces host translational shutoff and mRNA decay, with concomitant formation of stress granules and processing bodies - Raaben, Matthijs; Groot Koerkamp, Marian J. A.; Rottier, Peter J. M.; De Haan, Cornelis A. M. (Cellular microbiology, 2007)
Summary Many viruses, including coronaviruses, induce host translational shutoff, while maintaining synthesis of their own gene products. In this study we performed genome‐wide microarray analyses of the expression patterns of mouse hepatitis coronavirus (MHV)‐infected cells. At the time of MHV‐induced host translational shutoff, downregulation of numerous mRNAs, many of which encode protein translation‐related factors, was observed. This downregulation, which is reminiscent of a cellular stress response, was dependent on viral replication and caused by mRNA decay. Concomitantly, phosphorylation of the eukaryotic translation initiation factor 2α was increased in MHV‐infected cells. In addition, stress granules and processing bodies appeared, which are sites for mRNA stalling and degradation respectively. We propose that MHV replication induces host translational shutoff by triggering an integrated stress response. However, MHV replication per se does not appear to benefit from the inhibition of host protein synthesis, at least in vitro, since viral replication was not negatively affected but rather enhanced in cells with impaired translational shutoff.